Pendistribusian Dana Zakat Infak Sedekah (ZIS) untuk Pemberdayaan Masyarakat Studi Kasus BMT Amanah Ummah Sukoharjo - Sumarni Sumarni (ITB AAS INDONESIA Surakarta, 2018)
This study aims to determine: 1) The position of Baitul Mal at BMT Amanah Ummah 2) Model of financing BMT Amanah Ummah for the dhuafa (poor people). 3) Distribution of ZIS funds for community empowerment in BMT Amanah Ummah. This method of research used descriptive qualitative approach. This research was conducted in BMT Amanah Ummah Sukoharjo in June until August 2016. The subject of the study was Amil treasury of BMT Amanah Ummah. Informants were Baitul Mal employees and mustahiq. Method of collecting data was done by observation, interview and documentation. The results of this study, namely, 1) The separation of management between Baitul Mal and Baitul Tamwil. The Baitul Mal of BMT Amanah Ummah has its own manager and management. 2) Model of financing for the dhuafa at the Baitul Mal of BMT Amanah Ummah is to use qardhul hasan financing agreement, in the form of revolving fund used to finance or develop dhuafa’s bussiness. 3) The distribution of funds of Zakat Infak and Sedekah (ZIS) at Baitul Mal BMT Amanah Ummah is allocated to programs of empowerment, health, education and charity. A larger portion of fund is allocated to the development programs.